Agdc1p – a Gallic Acid Decarboxylase Involved in the Degradation of Tannic Acid in the Yeast Blastobotrys (Arxula) adeninivorans - Meier, Anna K.; Worch, Sebastian; Böer, Erik; Hartmann, Anja; Mascher, Martin; Marzec, Marek; Scholz, Uwe; Riechen, Jan; Baronian, Kim; Schauer, Frieder; Bode, Rüdiger; Kunze, Gotthard (Frontiers in Microbiology, 2017)
Tannins and hydroxylated aromatic acids, such as gallic acid (3,4,5-trihydroxybenzoic acid), are plant secondary metabolites which protect plants against herbivores and plant-associated microorganisms. Some microbes, such as the yeast Arxula adeninivorans are resistant to these antimicrobial substances and are able to use tannins and gallic acid as carbon sources. In this study, the Arxula gallic acid decarboxylase (Agdc1p) which degrades gallic acid to pyrogallol was characterized and its function in tannin catabolism analysed. The enzyme has a higher affinity for gallic acid (Km - 0.7 0.2 mM, kcat – 42.0 8.2 s-1) than to protocatechuic acid (3,4-dihydroxybenzoic acid) (Km – 3.2 0.2 mM, kcat – 44.0 3.2 s-1). Other hydroxylated aromatic acids, such as 3-hydroxybenzoic acid, 4-hydroxybenzoic acid, 2,3-dihydroxybenzoic acid, 2,4-dihydroxybenzoic acid and 2,5-dihydroxybenzoic acid are not gallic acid decarboxylase substrates. A. adeninivorans G1212/YRC102-AYNI1-AGDC1, which expresses the AGDC1 gene under the control of the strong nitrate inducible AYNI1 promoter achieved a maximum gallic acid decarboxylase activity of 1064.4 U/l and 97.5 U/g of dry cell weight in yeast grown in minimal medium with nitrate as nitrogen source and glucose as carbon source. In the same medium, gallic acid decarboxylase activity was not detected for the control strain G1212/YRC102 with AGDC1 expression under the control of the endogenous promoter. Gene expression analysis showed that AGDC1 is induced by gallic acid and protocatechuic acid. In contrast to G1212/YRC102-AYNI1-AGDC1 and G1212/YRC102, A. adeninivorans G1234 [Δagdc1] is not able to grow on medium with gallic acid as carbon source but can grow in presence of protocatechuic acid. This confirms that Agdc1p plays an essential role in the tannic acid catabolism and could be useful in the production of catechol and cis,cis-muconic acid. However, the protocatechuic acid catabolism via Agdc1p to catechol seems to be not the only degradation pathway.